A Diketopyrrolopyrrole‐Based Dimer as a Blue Pigment. Issue 11 (25th January 2019) - Casutt, Manuela; Dittmar, Benedikt; Makowska, Hanna; Marszalek, Tomasz; Kushida, Soh; Bunz, Uwe H. F.; Freudenberg, Jan; Jänsch, Daniel; Müllen, Klaus
Abstract: 1, 4‐Diketopyrrolo[3, 4‐ c ]pyrroles (DPPs) constitute a class of hydrogen‐bonded pigments covering a color range from yellow–orange to dark violet. We report facile dimerization of a Boc‐substituted 3, 6‐dithienyl‐DPP. The formed dimer shows brilliantly blue color as a result of the expansion of the chromophore. The soluble dimer acts as latent pigment and is converted to the corresponding pigment either via thermocleavage or acidic deprotection of the Boc groups. The synthesized pigment is characterized by high migrational stability in a polymer matrix and a clear blue color. Abstract : Blue with Boc : A Boc‐substituted 3, 6‐dithienyl‐DPP furnished a soluble latent pigment, which can be deprotected to give the blue dimeric DPP pigment.